"I can’t! I can’t! I can’t!" : un cri, un coup de feu "a shout and a shot" - Liliane Louvel (Caliban: French Journal of English Studies)
This paper will try to show how the book purports to be digging for the past, aiming at uncovering and recovering trauma, both collective and individual, thanks to recapturing the past for a character, for a reader, for a nation. The Wars, a novel by Timothy Findley, tries to make sense for the narrator but also for the reader of a founding image which opens the book and of other allegedly material images, photographs, interviews, archives. Robert Ross, a Canadian soldier who held a controversial role in the first World War, the war to end all wars, stands at the centre of this memorial reconstruction. Photographs, as described in the text, give rise to ekphraseis which often appeal to the reader’s sensitivity thanks to a detail which might correspond to what Roland Barthes described as the punctum. That is the sharp point which shoots from the photograph and pierces the ordinariness of the gaze, the studium. It leaves the horizontal plane of the image and rises up. It is the point of exchange between reception and emission and it introduces confusion in the spectator’s place. This is when image comes under view and when the traumatic symptom pierces the calm of everyday life with the eruption of the violence of an inhuman collective and personal past.